Optical direction motion and optical optimistic density with magnetic energy - Korpinar, Talat; Korpinar, Zeliha; Yeneroglu, Mustafa (Elsevier Gmbh, 2022)
In this paper, we present the notion of optical direction motion using optical quasi optimistic density. Thus, we describe optical direction potential magnetic energy of Lorentz forces. Also, we characterize new approach for optical electroosmotic magnetic phase in cold plasma. Finally, we obtain energy variation of the optical direction potential magnetic energy in Heisenberg group.
Keywords: Optical direction motion; Optical potential magnetic energy; Optical electroosmotic phase